Yoga-sūtra bhāṣya koṣaḥ = A concordance dictionary to The yoga-sūtra-s of Patanjali and The Bhāshya of Vyāsa - Das, Bhagavan, 1869-1958 (SAMP early 20th-century Indian books project, 1938)
Dictionary of yoga.